The Air Pollution and Its Impact on Cardiovascular Diseases - Latif, Hafizah; Wahyudi (Cardiovascular and Cardiometabolic Journal (CCJ), 2026)
Background: Air pollution has emerged as a significant global health concern, with over 99% of the world's population exposed to pollutants exceeding WHO-recommended levels. Cardiovascular diseases (CVDs) linked to air pollution include hypertension, atherosclerosis, arrhythmias, and heart failure, driven by mechanisms such as oxidative stress, autonomic imbalance, and systemic inflammation. Indonesia, ranking 18th globally for air pollution, faces severe challenges, with Jakarta recording PM2.5 levels nine times higher than WHO standards. Methods: This literature review synthesizes data from epidemiological studies, meta-analyses, and reports by organizations like WHO and the American Heart Association. It examines the impact of pollutants (PM2.5, NO2, CO, SO2, O3) on CVDs, explores biological pathways, and evaluates mitigation strategies. Data sources include the National Mortality and Morbidity Air Pollution Study (NMMAPS) and the European Society of Cardiology (ESC) guidelines. Aim: The study aims to highlight the cardiovascular risks of air pollution, analyze its pathophysiological mechanisms, and propose actionable strategies for individuals and governments. Recommendations include adopting renewable energy, improving public transport, enforcing stricter emissions regulations, and using protective measures like masks. By addressing air pollution, the study underscores the potential to reduce CVD morbidity and mortality, advocating for coordinated efforts to safeguard public health. --